Satellite Glial Cells in Pain Research: A Targeted Viewpoint of Potential and Future Directions - Gazerani, Parisa (Frontiers in Pain Research, 2021)
Chronic pain is known to be caused by sensitization within the pain circuits. An imbalance occurs between excitatory and inhibitory transmission that enables this sensitization to form. In addition to neurons, the contribution of central glia, especially astrocytes and microglia, to the pathogenesis of pain induction and maintenance has been identified. This has led to the targeting of astrogliosis and microgliosis to restore the normal functions of astrocytes and microglia to help reverse chronic pain. Gliosis is broadly defined as a reactive response of glial cells in response to insults to the central nervous system (CNS). The role of glia in the peripheral nervous system (PNS) has been less investigated. Accumulating evidence, however, points to the contribution of satellite glial cells (SGCs) to chronic pain. Hence, understanding the potential role of these cells and their interaction with sensory neurons has become important for identifying the mechanisms underlying pain signaling. This would, in turn, provide future therapeutic options to target pain. Here, a viewpoint will be presented regarding potential future directions in pain research, with a focus on SGCs to trigger further research. Promising avenues and new directions include the potential use of cell lines, cell live imaging, computational analysis, 3D tissue prints and new markers, investigation of glia–glia and macrophage–glia interactions, the time course of glial activation under acute and chronic pathological pain compared with spontaneous pain, pharmacological and non-pharmacological responses of glia, and potential restoration of normal function of glia considering sex-related differences.